Metagenomic insights into the dominant Fe(II) oxidizing Zetaproteobacteria from an iron mat at Lō´ihi, Hawai´l - Singer, Esther; Heidelberg, John F.; Dhillon, Ashita; Edwards, Katrina J. (Frontiers in Microbiology, 2013)
Zetaproteobacteria are among the most prevalent Fe(II) oxidizing bacteria at deep-sea hydrothermal vents; however, knowledge about their environmental significance is limited. We provide metagenomic insights into an iron mat at the Lōʻihi Seamount, Hawai’I, revealing novel genomic information of locally dominant Zetaproteobacteria lineages. These lineages were previously estimated to account for ~13% of all local Zetaproteobacteria based on 16S clone library data. Biogeochemically relevant genes include nitrite reductases, which were previously not identified in Zetaproteobacteria, sulfide:quinone oxidases, and ribulose-1,5-bisphosphate carboxylase (RuBisCo). Genes assumed to be involved in Fe(II) oxidation correlate in synteny and share 70% AASim with those previously identified in the related Zetaproteobacterium Mariprofundus ferrooxydans PV-1. Overall, Zetaproteobacteria genes appear to originate primarily from within the Proteobacteria and the Fe(II) oxidizing Leptospirillum spp. and are predicted to facilitate adaptation to a deep-sea hydrothermal vent environment in addition to microaerophilic Fe(II) and H2S oxidation. This dataset represents the first metagenomic study of Fe(II) oxidizing bacteria (FeOB) from an iron oxide mat at a deep-sea hydrothermal habitat.